تفسیر قرآن میں قرآن سے استفادہ کے حدود - محمد رضی الاسلام ندوی (FIKR-O NAZAR فکر ونظر, 2011)
Al-Quran - the Book of guidance for humanity was revealed to Muhammad (saw). The divine language of Al-Quran has its specific terminology and phrases. Each and every word of the Quran implies a number of meanings and stands for multi-shades of its perception. In the beginning these meanings were interpreted by the Prophet (saw) himself, by Sahaba and Tabien and later on by Mufasirin and Fuqaha. They devised and adopted their own methodologies of interpreting the words and ayaat of the Quran. One kind of the methodology is named Tafsir al-Quran bil Quran. It means interpreting ayaat and phrases of Quran with the help of other relevant ayaat and phrases in the Quran found in different places and sometimes in different contexts. This methodology identifies possible similarity of the meaning of two ayaat under reference. This article focuses on the parameters of this methodology for the interpretation of Quran. It includes the nature of methodology and possible ways of deducing meaning of similar ayaat and phrases of the Qran. This article narrates the merits and the significance of methodology highlighted by the scholars. The article also points out delicate difference between Nazm-e-Quran and Tafsir al-Quran Tafsir bil Quran. The writer emphasizes that adoption of this methodology does not mean rejection of other methodologies rather he warns emergence of mistakes in total rejection of other methodologies. He quoted a number of examples of the mistakes to make his argument.